Computational modeling and thermal analysis of magnetized nanofluid flow with physio-chemical interaction and chemical reaction between two non-parallel walls - Sohail, Shahid; Shah, Zahir; Rooman, Muhammad; Khan, Waris; Alshehri, Mansoor H.; Vrinceanu, Narcisa; Antonescu, Elisabeta (Frontiers in Chemistry, 2025)
The study of how energy undergoes changes in physio-chemical interactions involving Al2O3 and γ-Al2O3 with water and C2H6O2 within converging and diverging channels is of great significance, given its potential applications in today’s advanced technology. We have used two types of oxide nanoparticles, namely, Al2O3 and γ- Al2O3, with water and C2H6O2. The purpose of this study is to investigate an innovative comparative magnetohydrodynamic (MHD) nanofluid flow and heat transport with the impact of thermal radiation on water and ethylene glycol (EG) suspended with Al2O3 and γ-Al2O3 nanoparticles. A novel comparison of concentration of Al2O3–H2O, γ-Al2O3–H2O, and γ Al2O3–C2H6O2 nanofluids is investigated under the influence of chemical reactions. The system of nonlinear ordinary differential equations was obtained via a similarity transformation and then solved using the homotopy analysis method (HAM) in Mathematica. The temperature and velocity profiles are obtained numerically for a range of controlling parameter values, including the volume percentage φ of nanomaterials, the magnetic effect parameter M, the radiation parameter Rd, and Eckert number Ec in convergent/divergent channels. The concentration profiles of Al2O3–H2O, γ-Al2O3–H2O, and γ-Al2O3–C2H6O2 tri-nanofluids are calculated numerically for governing parameter values, including those accounting for chemical reactions. The investigation’s findings indicate that there is greater heat transport in γ-Al2O3–C2H6O2 and γ-Al2O3–H2O than in Al2O3–H2O. We have demonstrated that there is good agreement between the current results and those found in the literature for various values of the magnetic field parameter, thermal radiation parameter, and nanoparticle volume fraction.